The Routledge handbook of Muslim Iberia
1 online resource
Keywords: "This handbook offers an overview of the main issues regarding the political, economic, social, religious, intellectual and artistic history of the Iberian Peninsula during the period of Muslim rule (8th-15th centuries). A comprehensive list of primary and secondary sources attests the vitality of the academic study of al-Andalus (= Muslim Iberia) and its place in present-day discussions about the past and the present. The contributors are all specialists with diverse backgrounds providing different perspectives and approaches. The volume includes chapters dealing with the destiny of the Muslim population after the Christian conquest and with the posterity of al-Andalus in art, literature and different historiographical traditions. The chapters are organised in the following sections: Political history, concentrating on rulers and armies -- Social, religious and economic groups -- Intellectual and cultural developments -- Legacy and memory of al-Andalus. Offering a synthetic and updated academic treatment of the history and society of Muslim Iberia, this comprehensive and up-to-date collection provides an authoritative and interdisciplinary guide. It is a valuable resource for both specialists and the general public interested in the history of the Iberian Peninsula, Islamic and Medieval studies"--